2007
DOI: 10.1111/j.1600-6143.2007.01671.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppression for Dual Kidney Transplantation with Marginal Organs: The Old Is Better Yet

Abstract: Immunosuppressive protocols in dual kidney transplantation (DKT) are based on calcinerurin inhibitors (CNI). We wonder whether a CNI-free immunosuppression can improve outcome in older patients receiving a DKT with marginal donor organs. Thirty-six were treated with CsA, MMF and prednisone (CsA group) and 42 with rATG, SRL, MMF and prednisone (SRL group). Incidence of delayed graft function and acute rejection was 44% and 11% in the CsA group, and 40% and 8% in the SRL group. CMV infection incidence was low in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…6,17 Cruzado and associates 25 analyzed 2 groups of patients who received either cyclosporinebased immunosuppression (cyclosporine, mycophenolate mofetil, and prednisolone) or calcineurin-inhibitor-free protocol (thymoglobulin induction, sirolimus, mycophenolate mofetil, and prednisolone), and did not find differences in graft function or survival using calcineurin-inhibitor-free immunosuppression. Another paper compared calcineurin-inhibitor-free with cyclosporine-based immunosuppression protocols and reported significantly lower rates of delayed graft function (DGF) and a lower rate of cytomegalovirus infection in the sirolimus group with no difference in creatinine at 1 year.…”
Section: Immunosuppression Protocolmentioning
confidence: 99%
“…6,17 Cruzado and associates 25 analyzed 2 groups of patients who received either cyclosporinebased immunosuppression (cyclosporine, mycophenolate mofetil, and prednisolone) or calcineurin-inhibitor-free protocol (thymoglobulin induction, sirolimus, mycophenolate mofetil, and prednisolone), and did not find differences in graft function or survival using calcineurin-inhibitor-free immunosuppression. Another paper compared calcineurin-inhibitor-free with cyclosporine-based immunosuppression protocols and reported significantly lower rates of delayed graft function (DGF) and a lower rate of cytomegalovirus infection in the sirolimus group with no difference in creatinine at 1 year.…”
Section: Immunosuppression Protocolmentioning
confidence: 99%
“…Furthermore, there are an increasing number of elderly donors and recipients for KT (Wolfe et al, 2010; Abecassis et al, 2012). US initiatives, for example, have resulted in an increase in non-conventional sources of donors, such as expanded criteria donors (ECD) (Port et al, 2002; Stratta et al, 2006; Pascual et al, 2008; Klein et al, 2010), donors after cardiac death donation (DCD) (Howard et al, 2005; Abt et al, 2006; Farney et al, 2011), standard criteria donors (SCD) with warm ischemia times or prolonged cold (CIT) (Roodnat et al, 2003; Kayler et al, 2011; Kim et al, 2013; Debout et al, 2015; Xia et al, 2015), acute kidney injury (AKI) donors (Anil Kumar et al, 2006; Kayler et al, 2009; Farney et al, 2013; Hall et al, 2015; Heilman et al, 2015; Xia et al, 2015), double-kidney transplantation (DKT) and donors at the extremes of age (Johnson et al, 1996; Cruzado et al, 2007; De Serres et al, 2010; Fernández-Lorente et al, 2012). Recently, it was demonstrated that desensitization of the patient and subsequent transplantation with a kidney from an incompatible live donor increase the patient survival rate compared with those who remain on the waiting list for transplantation (Orandi et al, 2016).…”
Section: Alternative Management Of Kidney Diseasementioning
confidence: 99%
“…More recently, centers report censored graft survival rates, where patients who died with a functioning renal allograft are censored at the time of death. Using this methodology graft survival rates appear to be equal to, or possibly better in elderly individuals than in younger persons (21,(24)(25)(26)64). Death censored 1-and 3-year graft survival rates are estimated at 95.8% and 93.1% respectively.…”
Section: Patient and Graft Survivalmentioning
confidence: 99%
“…Data in regard to the use of IL-2 or antilymphocyte induction therapy are conflicting, and further work is required (5,33). Suggested new immune suppression protocols specifically tailored to the elderly individual have been advocated; however, few have been robustly evaluated in randomized controlled trials (24,28,32). Seniors are at higher risk of increased dependency for simple activities associated with healthy living.…”
Section: Posttransplantation Problems Specific To Elderly Patientsmentioning
confidence: 99%